The effect of long-range interactions on the infrared and Raman spectra of aragonite (CaCO3, Pmcn) up to 25 GPa - Gianfranco Ulian; Giovanni Valdrè (Scientific Reports, 2023)
Abstract Long-range interactions are relevant in the physical description of materials, even for those where other stronger bonds give the leading contributions. In this work, we demonstrate this assertion by simulating the infrared and Raman spectra of aragonite, an important calcium carbonate polymorph (space group Pmcn) in geological, biological and materials science fields. To this aim, we used Density Functional Theory methods and two corrections to include long-range interactions (DFT-D2 and DFT-D3). The results were correlated to IR spectroscopy and confocal Raman spectrometry data, finding a very good agreement between theory and experiments. Furthermore, the evolution of the IR/Raman modes up to 25 GPa was described in terms of mode-Grüneisen’s parameters, which are useful for geological and materials science applications of aragonite. Our findings clearly show that weak interactions are of utmost importance when modelling minerals and materials, even when they are not the predominant forces.